Research of NC Gear-hobbing Machining and Error Compensation - Jia Dongsheng; Zhao Jiali (Jixie chuandong)
According to the principles of various gear profile generation and gear generating error,the motion control structure of NC hobbing system for gear machining is optimized. The electronic composite differential unit is used to process the angle position pulse from the hobbing spindle and to process the motion coordinate（ or angle position） pulse from the workpiece axis. By means of position control and error compensation control unit,the on- line real time compensation of errors as tooh pitch division error,longitudinal tooth error,and tool wear error is realized. Meanwhile,the hobbing function of non- circular gear and axial modification gear（ small taper or drum type） is also expended.